2011
DOI: 10.2341/10-247-o
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Light Intensity Output of QTH and LED Curing Devices in Various Governmental Health Institutions

Abstract: Clinical Relevance Evaluating the intensity of a light curing unit regularly prior to the application of tooth-colored restorative materials is essential to assure the quality of restorative procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 27 publications
2
33
2
4
Order By: Relevance
“…A recent study has shown that many practitioners use halogen lights with power outputs ,300 mW/cm. 2,39 Thus, the polymer- ization efficiency achieved with high irradiance lights might be even more significant than was demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 46%
“…A recent study has shown that many practitioners use halogen lights with power outputs ,300 mW/cm. 2,39 Thus, the polymer- ization efficiency achieved with high irradiance lights might be even more significant than was demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 46%
“…It can be inferred that the same situation may exist in some research laboratories. Although some of these surveys used fiber-optic spectrometers to measure the output from the LCUs (Ernst et al 2006;Al Shaafi et al 2011), typically these surveys have been conducted with simple dental radiometers. While some dental radiometers may provide an accurate averaged radiant exitance value when used with an LCU from the same manufacturer, the reality is that the light output from LCUs can rarely be accurately measured and never completely described by a commercial dental radiometer (Leonard et al 1999;Aravamudhan et al 2006;Roberts et al 2006;Busemann et al 2008;Price et al 2012).…”
Section: Measuring Light Output: Radiant Power (W) and Radiant Exitanmentioning
confidence: 99%
“…38,39 To date, every study published that has evaluated light curing units (LCU) used in dental offices has shown that many are delivering an inadequate light output and are also poorly maintained. 40,41,42,43,44,45,46,47 In addition to being an averaged value that has been calculated from the power output divided by the tip area, the irradiance values stated by the manufacturers are usually measured only at the light tip. These values can give the dentist the impression they are using a "powerful" curing light, but significantly lower irradiance may be reaching the surface of the resin that is often at least 2 to 8 mm away from the light tip.…”
Section: Effect Of Light Tip To Resin Distancementioning
confidence: 99%